USING DELIBERATIVE DEMOCRACY TECHNIQUE TO IMPROVE NARRATIVE TEXT WRITING SKILL OF THE ELEVENTH GRADERS OF SMAN 2 MAGELANG IN THE SCHOOL YEAR 2015/2016 - Yulia Sugiarto; Sukarno Sukarno; Lilia Indriani (Faculty of Education and Teachers Training, 2018)
Writing is one of the compulsory skills that is tested in the final examination and it must be mastered by students of Senior High School. However, the eleventh graders of SMA N 2 Magelang still find difficulties in learning writing, especially in narrative text. It can be proved by the result of the average score of the writing test of 32 students, which was only 67.97. This score does not reach the minimum achievement criteria of 78. There are several factors influencing that condition. The writer conducted a research to overcome that problem by applying Deliberative Democracy Technique. There are two main objectives in the research. The first is to know whether Deliberative Democracy Technique can increase the learning motivation of narrative text writing skill. The second is to know how great the improvement of the narrative text writing skill after being taught by using Deliberative Democracy Technique of the eleventh graders of SMA N 2 Kota Magelang in the school year 2015/2016 is. The subject of the research is the eleventh graders of SMAN 2 Magelang, comprising 32 students. The writer conducted a classroom action research for this purpose. It was divided into three phases: Pre-cycle, Cycle I and Cycle II. The writer used non test (observation, questionnaire and documentation) and test as the instrument to collect the data. Based on the writer’s observation and questionnaires, it is showed that most students had behavioral change, they increase learning motivation.